Effect of lockdown on Students Studying in Various Colleges of Nursing - Jennifer W. Anthony, Deepak Sethi2 , Mangesh Jabade1 , Poonam Yadav1, Stephina Fernandes1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The pandemic has driven many countries in the world to freeze its economic, social and physicaldevelopmental activities, thus has affected the world in every possible ways. India is also imprison underthe tight lockdown. Government of India announced curfew on 22nd March, 2020 followed by 1st veryuncompromising lockdown phase led the country to put up the shutter in all sector. Additionally, it hasalso hit the educational sector. Many countries have decided close down institutes, this will definitely haveconsequences on skill growth. Considering the effects, the current study aims to assess effects of lockdownon nursing students and to find out the association of demographic details with effects of lockdown.Methodology: The study was conducted among the nursing college of Pune city and non-experimentaldescriptive research approach was done. The sample size for study was 60, selected by using non probabilityconvenience sampling technique from various students studying in nursing college in Pune city who metthe inclusion criteria. A structured modified questionnaire was developed based on the research problem, toget the information from the samples. It was divided in 2 sections; Section I consisted of items related todemographic variables of the study. Section II: Consisted of 15 questions to assess the effects of lockdownon various aspects i.e social, emotional, financial and academics in students studying in nursing colleges.Result: The analysis shows that 55% students were somewhat affected and 45% students were very muchaffected by the lockdown effects. 11.67% students were found to be not at all affected emotionally, 21.67%students were somewhat affected and 66.67% were found to be very much affected emotionally duringlockdown. 1.67% of students were not at all affected financially, whereas 66.67% students were somewhataffected and 31.67% students were very much affected by this crisis. Additionally, considering academics26.67% students were somewhat affected and 73.33% students were very much academically affected dueto this COVID-19 pandemic crisis. Since p-values corresponding only to year of programme is found to beless than 0.05, it shows association with lockdown effects.Conclusion: The current study concludes that COVID-19 has immensely affected Emotional, Financial andacademicals aspects of nursing students.